Modelling the influence of environmental factors on the physiological status of the Pacific oyster Crassostrea gigas in an estuarine embayment; The Baie des Veys (France) - Grangere, Karine; Menesguen, Alain; Lefebvre, Sébastien; Bacher, Cedric; Pouvreau, Stephane (Journal of Sea Research, 2009)
It is well known that temporal changes in bivalve body mass are strongly correlated with temporal variations in water temperature and food supply. In order to study the influence of the year-to-year variability of environmental factors on oyster growth, we coupled a biogeochemical sub-model, which simulates trophic resources of oysters (i.e. phytoplankton biomass via chlorophyll a), and an ecophysiological sub-model, which simulates growth and reproduction (i.e. gametogenesis and spawning), using mechanistic bases. The biogeochemical sub-model successfully simulated phytoplankton dynamics using river nutrient inputs and meteorological factors as forcing functions. Adequate simulation of oyster growth dynamics requires a relevant food quantifier compatible with outputs of the biogeochemical sub-model (i.e. chlorophyll a concentration). We decided to use the phytoplankton carbon concentration as quantifier for food, as it is a better estimator of the energy really available to oysters. The transformation of chlorophyll a concentration into carbon concentration using a variable chlorophyll a to carbon ratio enabled us to improve the simulation of oyster growth especially during the starvation period (i.e. autumn and winter). Once validated, the coupled model was a suitable tool to study the influence of the year-to-year variability of phytoplankton dynamics and water temperature on the gonado-somatic growth of the Pacific oyster. Four years with highly contrasted meteorological conditions (river inputs, water temperature and light) 2000, 2001, 2002 and 2003, were simulated. The years were split into two groups, wet years (2000 and 2001) and dry years (2002 and 2003). Significant variability of the response of oysters to environmental conditions was highlighted between the four scenarios. In the wet years, an increase in loadings of river nutrients and suspended particulate matter led to a shift in the initiation and the magnitude of the phytoplanktonic spring bloom, and consequently to a shift in oyster growth ...